Strengthening The Image of Madrasah Through The School Leadership System - Shodiq , Taufiq; Hefniy , Hefniy (Journal of Educational Management Research, 2022)
Today's society is more selective in choosing schools. This condition causes schools to compete with each other and show their existence. Educational institutions as service providers are required to prioritize the quality and output of their graduates. This research is aimed at analyzing the efforts of the principal of MTs Sirajul Ulum Krejengan in designing strategies to improve the school's good image in the community, as well as strategies in capturing the interest of prospective new students. This study uses a qualitative approach. Data collection techniques using interviews, observation and documentation. The formulation of school principal program planning in improving the school's image includes: (1) reviewing and identifying the various strengths and weaknesses of the school, namely by making continuous improvements by considering opportunities and threats to achieve the vision and mission; (2) improve physical and non-physical conditions; and (3) conducting promotions to the general public. Activation of school resources in improving the school's image is carried out by: (1) managing the needs, competencies, and harmonization of teachers and staff; (2) improve the standard of school facilities; (3) holding regular meetings; (4) strengthening the school administration system; (5) and improve the quality of services and education. Setting targets to improve the school's image, namely realizing Adiwiyata schools and improving the quality of education, and increasing public trust in the existence of schools; (6) besides that the target application was carried out late; (7) as well as an evaluation of activities that have been realized.